Beejal is solving the equation y/7 − 3 = 39.(1 point)

As a first step, he starts by adding
to both sides of the equation, and then continues by multiplying by
on each side.

1 answer

To solve the equation \( \frac{y}{7} - 3 = 39 \) step by step, let's follow Beejal's approach.

  1. Add 3 to both sides: \[ \frac{y}{7} - 3 + 3 = 39 + 3 \] This simplifies to: \[ \frac{y}{7} = 42 \]

  2. Multiply both sides by 7: \[ 7 \cdot \frac{y}{7} = 42 \cdot 7 \] This simplifies to: \[ y = 294 \]

So, Beejal first adds \( 3 \) to both sides and then multiplies by \( 7 \) on each side to get the solution \( y = 294 \).

Similar Questions
  1. Beejal is solving the equation y7 − 3 = 39.(1 point)As a first step, he starts by adding to both sides of the equation, and
    1. answers icon 2 answers
  2. beejal is solving the equation y/7 - 3 = 39as a first step, he starts by adding to both sides of the equation, and then
    1. answers icon 1 answer
  3. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions